The Relationship between Parental Attention Levels and Emotional Regulation in Early Childhood - Hidjanah, Hidjanah; Ferianti, Nurdini; Yulianty, Puji; Dirhadini, Aura Nabila (Kiddie: Early Childhood Education and Care Journal, 2026)
This study aims to analyze the effect of a lack of parental attention on early childhood emotional regulation, including children’s ability to manage, express, and stabilize their emotions. Phenomena observed in the school environment indicate that children who receive insufficient attention at home tend to display explosive emotional responses when their desires are not fulfilled. Using an explanatory quantitative correlational method, this study involved 20 children aged 4–6 years and 20 parents from an early childhood education institution (ECE) in Bogor Regency. Data were collected through Likert-scale questionnaires to measure parental attention and behavioral observation instruments to assess children’s emotional regulation. Descriptive statistical analysis showed that the average level of parental attention was 13.35, while the average score of children’s emotional regulation was 16.2. Correlation analysis yielded a coefficient of r = 0.727 (p < .001), indicating a statistically significant strong positive relationship between the two variables. These findings suggest that higher levels of parental attention are directly associated with better emotional regulation abilities in children. Conversely, minimal parental involvement causes children to lose emotional guidance, thereby hindering their social development and behavioral stability.